Influencia de los factores geoecológicos en la distribución de las especies forestales nativas del cantón Catamayo, provincia de Loja. - Veintimilla Rodas, Juan Antonio (2019)
This research aims at studying the influence of geo-ecological factors in the distribution of native forest species from Catamayo Canton, through the application of the statistical method of ecological profiles (CALCPERF) and geographic information systems (GIS) that was provided by SEMPLADES and the Municipality of Catamayo at a 1:25 000 scale. The work concerned the geo-referenced collection of secondary and field information both on location, and distribution of three species Sapindus saponaria L, Colicodendron scabridum (Kunth) Seem and Caesalpinia spinosa (Molina) Kuntze, then these data were represented cartographically by the application of GIS and relate them to the ecological factors (altitude, soil, geology, precipitation and mean annual temperature), for which classes or ranges of each analyzed factor were defined so to apply the method of ecological profiles and elaborate distribution maps and silvicultural zoning map, resulting in identification of three potential zones for the distribution of species, occupying an area of 13 329 ha, representing 20,45% of the total territory, which have ecological requirements necessary for distribution and optimal development. These results will provide information for future reforestation plans for the ecosystems of the inter-Andean dry valley of southern Ecuador. Keywords: ecological profiles, geographic information systems, silvicultural zoning.